2021
DOI: 10.1096/fj.202002697rrr
|View full text |Cite
|
Sign up to set email alerts
|

Association of the gut microbiota and fecal short‐chain fatty acids with skeletal muscle mass and strength in children

Abstract: chain fatty acids; TSM, total body lean soft tissue mass; TSM/TBF, the ratio of total body lean soft tissue mass to total body fat mass; TSMR, the ratio of total body lean soft tissue mass to weight; VA, valeric acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…It is well known that SCFAs can not only provide energy for the intestinal epithelial cells but also firmly maintain the morphology and function of the intestine ( 37 , 38 ). Moreover, SCFAs have also been confirmed to promote glucose intake and metabolism in skeletal muscle, and butyrate can improve the energy metabolism efficiency of muscle fibers ( 39 , 40 ). Based on the functions of the above bacterial families (fiber fermentation, inflammation mitigation, stress adaptation, and promotion of SCFAs on energy uptake and metabolism in skeletal muscle), it is speculated that these different bacterial families play a positive role in the performance of Thoroughbred horses.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that SCFAs can not only provide energy for the intestinal epithelial cells but also firmly maintain the morphology and function of the intestine ( 37 , 38 ). Moreover, SCFAs have also been confirmed to promote glucose intake and metabolism in skeletal muscle, and butyrate can improve the energy metabolism efficiency of muscle fibers ( 39 , 40 ). Based on the functions of the above bacterial families (fiber fermentation, inflammation mitigation, stress adaptation, and promotion of SCFAs on energy uptake and metabolism in skeletal muscle), it is speculated that these different bacterial families play a positive role in the performance of Thoroughbred horses.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study among healthy Chinese children reported that relationship of gut microbiome between muscle parameters was mediated by body fat content. 10 However, the cross‐sectional design of this study could not determine the temporal directionality of the association among fat mass, skeletal muscle mass and gut microbiota. Without validation of the temporal ordering of variables, the magnitude of the bias may be introduced by mediation analysis or conditioning on a collider, although we observed significant negative correlations between fat mass and SMI in both sexes.…”
Section: Discussionmentioning
confidence: 90%
“… 9 Recently, a few studies on the association between gut microbiota and muscle parameters have been reported. 10 , 11 , 12 To the best of our knowledge, however, no large population‐based study, including young‐ and middle‐aged individuals, has investigated the association of gut microbiota with skeletal muscle mass. In addition, various previous studies have shown a strong association between sex and loss of muscle mass on human health, 9 and sex specificity is known to influence the composition of the gut microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle oxidative metabolism, glucose uptake, and insulin sensitivity appear to be enhanced by SCFA administration [ 53 ]. SCFAs are associated with skeletal muscle mass and strength in pediatric populations [ 54 , 55 ]. Individuals with lower concentration of butyric acid had lower handgrip strength [ 56 ].…”
Section: Discussionmentioning
confidence: 99%